Electrofishing in streams of low water conductivity but high biodiversity value: Challenges, limits and perspectives. (9th September 2019) - Pottier, Gaetan; Beaumont, William R.; Marchand, Frédéric; Le Bail, Pierre‐Yves; Azam, Didier; Rives, Jacques; Vigouroux, Régis; Roussel, Jean‐Marc
Abstract: Electrofishing in streams of low water conductivity has technical limitations leading to the widespread use of poison fishing. In theory, provided a high enough voltage gradient can be created in water, electrofishing should be possible in all but the lowest of conductivities (<10 µS/cm). Using custom‐made equipment delivering up to 1, 500 V DC, tests were carried out in French Guiana on 27 streams with water conductivity as low as 16 µS/cm. Approximately 5, 800 fish of 93 species were captured, with an electrofishing mortality rate of 1.83%. Poison treatments were used within enclosed sections to assess how efficient multiple pass electrofishing removal is when assessing species richness and population number. The Chao II estimator on 2 electrofishing passes gave the best results for species richness, but rare species can elude electrofishing. Estimates of total fish abundance (i.e. all species pooled) were possible with the use of depletion models. Capture efficiencies by species were highly biased, however, and abundance could be underestimated for the most difficult species to catch. These results show that with the right equipment and settings, electrofishing can be an efficient alternative to poison fishing surveys in small tropical streams of low water conductivity but high biodiversity value.